Rozwój rosyjskiego zagłębia południowego w latach 1795-1899 w opinii "Przeglądu Technicznego" - Kowalczyk, Rafał Wiktor (Acta Universitatis Lodziensis. Folia Historica, 2003)
Decline of XVIII century brought interest the region o i Russia named later the Coal-basin Donieck. One of the first who were interested in this region was the omnipotent minister Russian tzarina Catherine II, duke Grigorij Aleksandrowich Potiomkin. However, the actors of technology and communication made the development of heavy industry impossible at this area. The geological investigations led to discovery of ledges of pit-coal and coking-coal on the territory of Donieck in 1790. The government initiatives concerning the development of region of Donieck based on local dePosits of pit-coal and iron-stone failed. Situation of private investments was similar. Factories of "Noworossyjskie Company” (British capital) and Pastuchow’s (Russian capital) founded in the Coal-basin of Donieck functioned only with support of subsidies of the government. The economic torpor of southern Russia ended in the second half of 1870s. It was caused discovery of the deposits of high-quality iron-stone in area or Krivoi Rog by local businessman Alexander Pohl. The change of economic doctrine of Russian Empire in 1877 caused the inflow or foreign capitals into the region. The govemement made foreign investors locate huge means for building modern railway lines. They connected southhern Russia with leading markets of Russian Empire. The true investment boom in southern Russia took place atter 1886 when government increased custom duties for iron and import became unprofitable. Period of economic situation or 1890s led to development of region of “Niz Dnieprowski” and “the Coasts or Azov See”. All the investments in southern Russia were based on estimated data about deposits or high-grade iron-stone of Krivoi Rog. Using up or the richest deposits of iron-stone in area of Krivoi Rog caused that exploitation of worse iron-stone of Kercz region begun in 1898. The profits generated by joint-stock companies in southern Russia let them introduce newest technologies. The southern region or Russian Empire was the most modern centre of industry. This caused using the by-products and development of chemical industry there. In the middle of 1890s there was a great technological difference between the mining of iron-stone of Krivoi Rog and coal-mining of the Coal-basin of Donieck. It was the result of shallow and rich deposits of pit-coal in the Coal-basin of Donieck. Using up of these deposits caused that in the middle of 1890s the modern technological solutions in coal mining were introduced. In the same period the modern systems of iron-stone mining functioned exclusively in Krovoi Rog. The dynamic development of production of steel and steel rails in southern Russia caused demand for ferro-manganese and matcrrial mirror. Russia was world largest manufacturer of manganic ore. The largest deposits were in district of Kutay and Ekaterynoslaw (nikopolska and caucasian ore). In the middle of 1890s in southern Russia the production of ferro-manganese and material mirror was started. As the result of foreign capital investments the southern centre fransformed into the largest complex of heavy industry in Russia. In years 1870-1900 the coal production increased from 32,8 to 69,5% and output of iron-stone form 2,8 to 57,2%. In the same period the production of pig-iron increased from 1,4 to 51,8%. In years 1880-1900 the production of iron and steel increased from 4,5 to 44,0%.